Rice tolerance to fluridone at different application timings and in mixtures with commonly used herbicides - Maria C. C.R. Souza; Jason K. Norsworthy; Thomas R. Butts; Robert Scott (Weed Technology)
Introducing new herbicides requires a comprehensive understanding of how crops respond to various herbicide-related factors. Fluridone was registered for use in rice production in 2023, but research on rice tolerance to this herbicide is lacking. Hence, field research aimed to 1) evaluate the effect of fluridone application timing on rice tolerance and 2) assess rice response to fluridone in a mixture with standard rice herbicides applied to 3-leaf rice. Both experiments were conducted in a delay-flooded dry-seeded system using a randomized complete block design, with four replications. Treatments in the first experiment included a nontreated control and 10 application timings, ranging from 20 d preplant to postflood. The second experiment had a two-factor factorial structure, with factor A being the presence/absence of fluridone, and factor B being herbicide partners, including bispyribac-sodium, fenoxaprop, penoxsulam, propanil, quinclorac, quizalofop, and saflufenacil. In the first experiment, the maximum injury in 2022 was 28%, caused by the preemergence treatment. In 2023, fluridone applied preemergence caused the greatest injury (42%) 2 wk after flood establishment, declining to 37% in late season (13 d before rice reached 50% heading). Yield reductions of 21% occurred with the delayed preemergence treatment in 2022 and 42% with the preemergence treatment in 2023. Mixing fluridone with standard herbicides increased rice injury by no more than eight percentage points compared with the herbicides applied alone. Additionally, no adverse effects on rice groundcover or grain yield resulted from fluridone in the mixture. These results indicate a need to avoid fluridone applications near planting because of negative impacts on rice. Furthermore, fluridone can be mixed with commonly used rice herbicides, offering minimal risk to rice.